Preface - Kumam, Poom; Cho, Yeol Je; Gopal, Dhananjay (Communications in Mathematics and Applications, 2016)
The Asian Conference on Fixed Point Theory and Optimization (ACFPTO) series is an international research conference that is held every two-year in Thailand, and is aimed mainly to be a central conference for fixed point and optimization theorists in Asia. Despite the title of the conference, it is also widely open for inter-disciplinary areas of interests. The 9th ACFPTO was successfully held at King Mongkut’s University of Technology by May 18-20, 2016. Originally, the conference was national scaled, focused only on fixed point theory and applications and was held annually. With the fast growth of fixed point theorists in Thailand, researchers were able to discuss and collaborate with each others more easily - resulted in rapid development of the theory and also open new possibilities of extending the research scope into other neighborhood topics, and finally resolved into the present series of conference. This special issue proceedings will be an option for publishing novel original research articles for fellow researchers in related fields to study recent developments by the contributions of researchers especially from Asia. Poom Kumam, Yeol Je Cho and Dhananjay Gopal (November 14, 2016)